PER1 Is a Prognostic Biomarker and Correlated With Immune Infiltrates in Ovarian Cancer - Chen, Mali; Zhang, Lili; Liu, Xiaolong; Ma, Zhen; Lv, Ling (Frontiers in Genetics, 2021)
Background :Period circadian protein homolog 1(PER1) is an important component of the biorhythm molecular oscillation system and plays an important role in the development and progression of mammalian cancer. However, the relationship between PER1 and Ovarian cancer (OV) prognosis is currently unclear. Methods :Oncomine and Timer databases were used to examine the expression of PER1 in OV. Kaplan-Meier plotter、Prognoscan were used to evaluate the relationship between PER1 and the prognosis. Kaplan-Meier plotter was used to analyze the relationship between PER1 and the clinicopathological features of ovarian cancer. The relationship between PER1 expression and immune infiltration in OV was investigated using the Timer database and Cibersort algorithm. Use STRING online tool to analyze PER1 related protein functional groups, and use Genemania online tool to analyze gene groups with similar functions to PER1. Use NetworkAnalyst to analyze transcription factors that regulate PER1. The correlation between PER1 and immunoinvasion of ovarian cancer was analyzed by TIMER database.Finally, quantitative real-time polymerase chain reaction (qRT-PCR) was performed for detecting PER1 expressions .Results: PER1 is expressed differently in different cancer tissues, and its expression in various subtypes of OV is lower than that in normal ovarian tissue.The overall survival rate of OV patients with low PER1 expression is reduced.The decreased expression of PER1 in stage1, stage1+2 and other clinical types is related to the poor prognosis of OS, while the increased expression of PER1 in stage3+4, TP53 mutation is related to the poor prognosis of OS and PFS. Eight genes with higher correlation with PER1 were found, and finally find four transcription factors regulating PER1 and eight related genes. In OV, the expression of PER1 is positively correlated with the level of cell infiltration such as Neutrophil, Treg, Macrophage M2, and is closely related to a variety of immune markers. In decreased CD8+ memory T cells, decreased Treg cells and other lymphocyte subsets, the high expression of PER1 is significantly related to poor prognosis. Reduced expression of PER1 was significantly associated with poor overall survival. Conclusion: PER1 can be used as a prognostic biomarker for determining the prognosis and immune infiltration of OV.